ANALISIS STRATEGI PEMASARAN DIGITAL DALAM MENINGKATKAN VOLUME PENJUALAN AYAM PETELUR DI UD MABBARAKKAE KABUPATEN SIDENRENG RAPPANG - Muh. Irgi Darmawan; Andi Riska Andreani Syafaruddin; Haslindah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Increasingly competitive business conditions have made marketing strategy a crucial factor for business growth, including in the food sector such as commercial layer egg sales. This study aims to describe the marketing strategy implemented by UD Mabbarakkae and to analyze the contribution of marketing mix elements to the sales volume of commercial eggs in Sidenreng Rappang Regency. The study employed a qualitative descriptive approach with a single case study design. Data were collected through direct observation, in-depth interviews, documentation, and literature review involving eight informants consisting of the business owner, employees, and customers, selected using purposive sampling. Data were analyzed following the Miles and Huberman model, comprising data reduction, data display, and conclusion drawing/verification, assisted by NVivo 12 software for systematic coding and thematic grouping. The results show that, within the marketing strategy variable (7P marketing mix), the people indicator obtained the highest percentage (23.89%), followed by process (15.93%), place (14.16%), price (13.27%), promotion and physical evidence (12.39% each), and product (7.96%). For the sales volume variable, the market capability indicator was the most dominant (40.82%), followed by market condition and capital (28.57% each), and market organization (2.04%). These findings indicate that the integrated implementation of the 7P marketing mix, particularly through service quality, effective processes, and ease of product access, has contributed positively to the increase in sales volume at UD Mabbarakkae.